Fetal axillary lymphangioma - Coutada, Rosalia S.; Silva, Joao P.; Ribeiro, Domingos C.; Pinheiro, Paula M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Lymphangioma is a rare congenital malformation of the lymphatic system that occur in 1 per 6000 live births. The most common site of lymphangioma is the neck (also named cystic hygroma), accounting for 75% of the cases, and it is strongly related to aneuploidies. Axillary location is very rare and appears not to be associated with chromosomal abnormalities. Tumor growth, fetal anemia secondary to intralesional bleeding, hydrops fetalis and shoulder dystocia are possible obstetric complications of this condition. The prognosis is generally good in the absence of abnormal karyotype, fetal hydrops or extension of the lymphangioma to adjacent tissues. Surgical excision or sclerotherapy are the main treatment choices. The authors present a case of a right fetal axillary lymphangioma and review the literature.